Uyghur Nation Reform and Revolution on the Russia-China Frontier - Brophy, David (Harvard University Press, 2016)
Along the Russian-Qing frontier in the nineteenth century, a new political space emerged, shaped by competing imperial and spiritual loyalties, cross-border economic and social ties, and revolution. David Brophy explores how a community of Central Asian Muslims responded to these historic changes by reinventing themselves as the Uyghur nation
Description based on online resource; title from PDF title page (publisher's Web site, viewed 01. Dez 2022)
Keywords: HISTORY / Asia / China; Uighur (Turkic people) -- Ethnic identity; Uighur (Turkic people) -- History; Uighur (Turkic people) -- Politics and government